A review of the impact of financing mechanisms on maternal health care in Australia - Haylee Fox; Stephanie M. Topp; Emily Callander; Daniel Lindsay (BMC, 2019)
Abstract Background The World Health Organization states there are three interrelated domains that are fundamental to achieving and maintaining universal access to care - raising sufficient funds for health care, reducing financial barriers to access by pooling funds in a way that prevents out-of-pocket costs, and allocating funds in a way that promotes quality, efficiency and equity. In Australia, a comprehensive account of the mechanisms for financing the health system have not been synthesised elsewhere. Therefore, to understand how the maternal health system is financed, this review aims to examine the mechanisms for funding, pooling and purchasing maternal health care and the influence these financing mechanisms have on the delivery of maternal health services in Australia. Methods We conducted a scoping review and interpretative synthesis of the financing mechanisms and their impact on Australia's maternal health system. Due to the nature of the study question, the review had a major focus on grey literature. The search was undertaken in three stages including; searching (1) Google search engine (2) targeted websites and (3) academic databases. Executive summaries and table of contents were screened for grey literature documents and Titles and Abstracts were screened for journal articles. Screening of publications' full-text followed. Data relating to either funding, pooling, or purchasing of maternal health care were extracted for synthesis. Results A total of 69 manuscripts were included in the synthesis, with 52 of those from the Google search engine and targeted website (grey literature) search. A total of 17 articles we included in the synthesis from the database search. Conclusion Our study provides a critical review of the mechanisms by which revenues are raised, funds are pooled and their impact on the way health care services are purchased for mothers and babies in Australia. Australia's maternal health system is financed via both public and private sources, which consequentially creates a two-tiered system. Mothers who can afford private health insurance - typically wealthier, urban and non-First Nations women - therefore receive additional benefits of private care, which further exacerbates inequity between these groups of mothers and babies. The increasing out of pocket costs associated with obstetric care may create a financial burden for women to access necessary care or it may cause them to skip care altogether if the costs are too great.